Refugee Integration in Germany: The Interplay of Othering, Digital Exclusion, and Identity Negotiation - Miriam Berg (14771470) (2025)
This study explores the multifaceted experiences of refugees in Hamburg, Germany, with a focus on how various forms of othering—social, cultural, linguistic, and digital—affect their integration. Through qualitative interviews with 62 refugees, the findings reveal that language acquisition, while often regarded as essential for integration, does not shield refugees from exclusion. Othering extends beyond linguistic differences, intersecting with gender, race, and religious identity, further complicating integration efforts, particularly for women. Additionally, the study identifies digital exclusion as another form of othering, termed “digital othering,” which restricts refugees’ access to social and economic participation while adversely affecting their psychological well-being and identity formation. Despite these challenges, refugees exhibit significant self-agency in navigating social and digital barriers. The findings underscore the need for a comprehensive approach to integration that transcends language proficiency and economic participation, addressing both social and digital forms of othering. This study calls for policies promoting equitable digital access, transforming digital spaces into platforms for empowerment, and fostering a more inclusive society. Drawing on social identity theory and the concept of othering, the research shows how societal narratives and digital exclusion intersect to shape refugee integration, advocating for inclusive strategies to tackle systemic inequalities. Other Information Published in: Journal of International Migration and Integration License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s12134-025-01238-0